Odpowiedzi

2010-04-13T18:21:06+02:00
10.
a)
0,5x - 4 = x - 6 mnożymy przez 2
x - 8 = 2x - 12
-x = -4
x = 4
b)
x - 5 = 1/3x + 1 mnożymy przez 3
3x - 15 = x + 3
2x = 18
x = 9
c)
x/4 - 1/4 = 2 mnożymy przez 4
x - 1 = 2
x = 3
d)
x/5 - 3 = x + 1/5 mnożymy przez 5
x - 15 = 5x + 1
-4x = 16
x = -4
e)
5/6 (x-1) = 4 mnożymy przez 6
5x - 5 = 24
5x = 29
x = 29/5
f)
-0,5 (-x-6) = -x mnożymy razy -2
-x-6 = 2x
-3x = 6
x = -2

zad 11
a)
2x+3 / 5 = 2-x / 3 - x mnożymy przez 15
6x + 9 = 10 - 5x - 15x
26x = 1
x = 1/26
b)
(x+1) / 2 - (x-1) / 3 = 1/4 mnożymy przez 12
6x + 6 - 4x + 4 = 3
2x = -7
x = -3,5
c)
mnożymy przez 6
12x + 21 - 5x + 1 = 6x + 30
x = 8
d)
mnożymy przez 8
2x + 10 - 2x - 1 = 8 - 4x
4x = -1
x = -1/4
2 5 2
2010-04-13T18:27:24+02:00
Zad 10
a) 1/2x-4=x-6
1/2x - x=-6+4
-1/2x=-2 |:(-1/2)
x= 4

b) x-5=1/3x+1
x-1/3x=1+5
-2/3x=6|:(-2/3)
x= 6*(-3/2)
x=-9

c) x/4 - 1/4 = 2| *4
x-1=8
x=8+1
x=9

d)x/5 - 3 = x + 1/5 |*5
x-15=5x+1
x-5x=1+15
-4x=16/:(-4)
x=-4

e) 5/6(x-1)=4
5/6x-5/6=4 |*6
5x-5=24
5x=24+5
5x=29/:5
x=29/5

f) -1/2(-x-6)=-x
1/2x+3=-x
1/2x+x=-3
1,5x=-3 |:1,5
x=2

zad 11
a) 2x+3/5= 2-x/3 -x |*15
3(2x+3)=5(2-x)-15x
6x+9=10-5x-15x
6x+5x+15x=10-9
26x=1/:26
x=1/26

b) x+1/2 -x-1/3 = 1/4 |*12
6(x+1)- 4(x-1)=3
6x+6-4x+4=3
6x-4x=3-6-4
2x=-7/:2
x=-3,5

c) 4x+7/2 - 5x-1/6= x+5 |*6
3(4x+7)-5x-1=x+5
12x+21-5x-1=x+5
12x-5x-x=5-21
6x=-16/:6
x=-16/6
x= - 8/3

d) x+5/4 - 2x+1/8 = 1/2 (2-x)
x+5/4 - 2x+1/8=1-x |*8
2(x+5)- 2x+1=1-x
2x + 10 - 2x+1 =1-x
2x-2x+x=1-1-10
x=-10



| - kreska dzielenie lub mnożenia
/ - kraska ułamkowa
1 5 1